Comparative Evaluation of Postoperative Recovery and Complication Rates in Patients Undergoing Laparoscopic Versus Open Abdominal Surgeries Under General Anesthesia - Faisal Toheed, Samreen Siddique, Rooh Ali, Faiza Hameed, Khushal Khan, Muhammad Iqbal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Abdominal surgeries constitute a large proportion of general surgical procedures, and the choice of operative technique directly affects recovery and complication rates. Open surgery, the traditional approach, provides good exposure but is associated with increased postoperative pain, prolonged hospital stay, and higher morbidity. Laparoscopic surgery, introduced as a minimally invasive alternative, has shown potential benefits, yet comparative evaluations under similar anesthetic conditions remain important, especially in low- and middle-income healthcare settings. Objective: To compare postoperative recovery and complication rates in patients undergoing laparoscopic versus open abdominal surgeries under general anesthesia. Methods: A prospective observational study was carried out in the Department of General Surgery at Pakistan Institute of Medical Sciences (PIMS), Islamabad, and Bolan Medical Complex Hospital, Quetta, from January 2023 to June 2023. A total of 120 patients were enrolled, with 60 undergoing laparoscopic and 60 undergoing open procedures. Data on demographic variables, operative time, postoperative pain assessed at 24 hours using the Visual Analog Scale (VAS), time to ambulation, length of hospital stay, and complications were collected and analyzed using SPSS version 26. A p-value <0.05 was considered statistically significant. Results: Operative time was longer in laparoscopic procedures (95 ± 12 minutes) compared with open surgeries (85 ± 10 minutes, p = 0.03). However, laparoscopic patients had lower postoperative pain scores (VAS 3.2 ± 1.1 vs. 6.1 ± 1.3), earlier ambulation (12 ± 3 vs. 24 ± 5 hours), shorter hospital stays (3.4 ± 0.9 vs. 7.1 ± 1.2 days), and fewer complications (10% vs. 28%, p = 0.01). Conclusion: Laparoscopic abdominal surgery offers improved recovery and reduced complications compared to open surgery and should be the preferred approach for elective procedures where feasible. Keywords: Laparoscopic surgery, Open surgery, Postoperative recovery, Complications, General anesthesia